Physiochemical properties of combustion synthesized La0.6Sr0.4Co0.8Fe0.2O3−δ perovskite: A role of fuel to oxidant ratio. (December 2015) - Jamale, Atul P.; Shanmugam, Sangaraju; Bhosale, C.H.; Jadhav, L.D.
Abstract: The solution combustion synthesis is a novel approach to synthesize the nanocrystalline materials with an unexpectedly high surface to volume ratio. Thus, in present paper, La0.6 Sr0.4 Co0.8 Fe0.2 O3− δ powders have been synthesized by solution combustion synthesis route at different fuel to oxidant ratio ( ψ ) and its effect on different physiochemical properties have been studied. The mode of propagation of combustion reaction changed from smoldering to volume with increasing ψ . The thermal analysis shows that exothermicity increased with ψ resulting into enhanced agglomeration as confirmed from particle size distribution. Typically, the size of agglomerate varies from 0.59 to 1.56 μm. The XRD and FT-IR patterns reveal that the phase pure La0.6 Sr0.4 Co0.8 Fe0.2 O3−δ is formed at the ψ =2. The TEM particles size is 25 nm. La0.6 Sr0.4 Co0.8 Fe0.2 O3−δ powder shows the higher catalytic activity at about 426 °C.